Development of a rapid, simple, and sensitive point-of-care technology platform utilizing ternary NanoLuc - Torio, Emily A.; Ressler, Valerie T.; Kincaid, Virginia A.; Hurst, Robin; Hall, Mary P.; Encell, Lance P.; Zimmerman, Kristopher; Forsyth, Stuart K.; Rehrauer, William M.; Accola, Molly A.; Hsu, Chia-Chang; Machleidt, Thomas; et al. (Frontiers in Microbiology, 2022)
Point-of-care tests are highly valuable in providing fast results for medical decisions for greater flexibility in patient care. Many diagnostic tests, such as ELISAs, that are commonly used within clinical laboratory settings require trained technicians, laborious workflows, and complex instrumentation hindering their translation into point-of-care applications. Herein, we demonstrate the use of a homogeneous, bioluminescent-based, split reporter platform that enables a simple, sensitive, and rapid method for analyte detection in clinical samples. We developed this point-of-care application using an optimized ternary, split-NanoLuc luciferase reporter system that consists of two small reporter peptides added as appendages to analyte-specific affinity reagents. A bright, stable bioluminescent signal is generated as the affinity reagents bind to the analyte, allowing for proximity-induced complementation between the two reporter peptides and the polypeptide protein, in addition to the furimazine substrate. Through lyophilization of the stabilized reporter system with the formulated substrate, we demonstrate a shelf-stable, all-in-one, add-and-read analyte detection system for use in complex sample matrices at the point-of-care. We highlight the modularity of this platform using two distinct SARS-CoV-2 model systems: SARS-CoV-2 N antigen detection for active infections and anti-SARS-CoV-2 antibodies for immunity status detection using chemically conjugated or genetically fused affinity reagents, respectively. This technology provides a simple and standardized method to develop rapid, robust, and sensitive analyte-detection assays with flexible assay formatting making this an ideal platform for research, clinical laboratory, as well as point-of-care applications utilizing a simple handheld luminometer.